Terrorism on Dark Web (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, everyone has access to a burst of data in Cyberspace. The classic Web or Clear web consists of all the sites Internet and pages that are indexed by search engines conventional research; however, it only represents 5% of the entire web. Despite the multiple Internet advantages, it can hide several threats for nations and people, such as blackmail, illegal drugs and arms sales and murder. This side is the dark side of Internet which includes illegal activities starting from bullying to terrorism. In this paper, we define the Dark Web (DW) and who are the users of this part of cyberspace. We define dark web and emphasize illegal activities related to it. Our study focuses on cyber terrorism activities. Additionally, we define what is cyber terrorism? Who are the responsible of it and why this phenomenon has been exacerbate in the last few years? Moreover, present efforts done by international and national organization to combat against this phenomenon